ANALISIS TINGKAT KERENTANAN PENCEMARAN AIR TANAH PADA WILAYAH PENAMBANGAN DAN PENGOLAHAN EMAS RAKYAT DESA PANCURENDANG, KABUPATEN BANYUMAS - Muryani, Eni; Rahmah, Dayu Aviana; Santoso, Dian Hudawan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2019)
The people's gold mining and processing activities have an impact on the surrounding environment. Some residents immediately dispose of waste from gold processing into the environment. Therefore, analysis of the level of vulnerability of pollution is needed to determine the size of the level of difficulty and ease of contaminated substances to influence water quality, both surface water and groundwater. The purpose of this study was to analyze the level of vulnerability of groundwater pollution around the study area. The method used in this research is survey method and field mapping, sampling method: purposive sampling, laboratory analysis method, mathematical method, and descriptive evaluation method. The calculation to determine the level of vulnerability of pollution is the DRASTIC method for groundwater vulnerability with 7 parameters, namely groundwater depth, rainfall, aquifer type, soil texture, slope, slope, unsaturated zone type, and hydraulic conductivity. Based on the results of the study it was known that the study area had 2 classifications of the level of vulnerability of groundwater pollution, namely the moderate and high classification. Areas that are located in the direction of groundwater flow and are lower than pollutant sources will potentially be more polluted.   Keywords : DRASTIC, Pollution, Groundwater, Gold Mine